The protective effect of influenza vaccine in a mixed influenza A and B epidemic in a boys' boarding school - Briscoe, J. H. D. (1977)
A mixed influenza A and B epidemic, which affected 30 per cent of the boys in a boarding school during the early part of 1976 is described. Virological findings indicate that most cases were due to influenza viruses similar to A/Victoria/75. The incidence of influenza was similar in all blocks in the school, but very variable in the boys' houses. The four-day half-term holiday helped to limit the epidemic. Eighty-six per cent of the boys had received an influenza vaccine containing the A/Scotland and A/Port Chalmers antigens. Influenza vaccination was of definite value, giving a protection rate among vaccinated boys of 36 per cent. Vaccinated boys who developed influenza had a shorter illness than unvaccinated boys.